DETERMINANT FACTORS OF THE ENVIRONMENTAL DISCLOSURE LEVEL IN BRAZILIAN LARGEST TRANSNATIONALS IN 2014 ACCORDING TO DOM CABRAL FOUNDATION - Barbosa Batista, Antonio; Vasconcelos Silva Cruz, Naiana; Leal Bruni, Adriano (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
This study analyzes which variables can influence the environmental divulgation level among the 52 largest Brazilian transnational organizations in 2014, according to the Dom Cabral Foundation. This is an exploratory-descriptive and documentary study, with a quantitative approach, whose data collection was based on the sustainability annual reports and reference forms published in the period from 2013 to 2014 by the analyzed organizations and published on the site of BM & FBOVESPA and its institutional sites. Multiple linear regression was used for data analysis. The results showed that the internationalization degree is a significant factor for the environmental divulgation level, confirming the point of view that the greater the existing Transnationality ties, the greater the companies' search for alternatives capable of establishing guarantees related to the strengthening of relations with its stakeholders. However, aspects such as size, indebtedness, activity sector and performance were not relevant.